ATP7A-dependent copper sequestration contributes to termination of β-CATENIN signaling during early adipogenesis - H. Yang; E. Kabin; Y. Dong; X. Zhang; M. Ralle; S. Lutsenko (Elsevier, 2024)
Objectives: Adipocyte fate determination is tightly regulated by extrinsic signaling pathways and intrinsic metabolic and morphologic changes that maintain adipose tissue function. Copper (Cu) homeostasis is required for the normal metabolism of mature adipocytes, whereas the role of Cu in adipogenesis is unclear. Methods: To determine the role of Cu is adipocytes differentiation, we used 3T3-L1 adipocytes, immunocytochemistry, X-ray fluorescence, mass-spectrometry, pharmacological treatments, and manipulations of copper levels. Results: In differentiating 3T3-L1 cells, adipogenic stimuli trigger the upregulation and trafficking of the Cu transporter Atp7a, thus causing Cu redistribution from the cytosol to vesicles. Disrupting Cu homeostasis by the deletion of Atp7a results in Cu elevation and inhibition of adipogenesis. The upregulation of C/EBPβ, an initial step of adipogenesis, is not affected in Atp7a−/− cells, whereas the subsequent upregulation of PPARγ is inhibited. Comparison of changes in the Atp7a−/− and wild type cells proteomes during early adipogenesis revealed stabilization of β-catenin, a negative regulator of adipogenesis. Cu chelation, or overexpression of the Cu transporter ATP7B in Atp7a−/− cells, restored β-catenin down-regulation and intracellular targeting. Conclusions: Cu buffering during early adipogenesis contributes to termination of β-catenin signaling. Abnormal upregulation of β-catenin was also observed in vivo in the livers of Atp7b−/− mice, which accumulate Cu, suggesting a tissue-independent crosstalk between Cu homeostasis and the Wnt/β-catenin pathway. These results point to a new regulatory role of Cu in adipocytes and contribute to better understanding of human disorders of Cu misbalance.